2008
DOI: 10.1021/ac801662n
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and Imaging of Lipids on Brain and Liver Tissue by Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Using 2-Mercaptobenzothiazole as a Matrix

Abstract: 2-Mercaptobenzothiazole (MBT) is employed for the first time as a matrix for the analysis of lipids from tissue extracts using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. We demonstrate that the performance of MBT is superior to that of the matrixes commonly employed for lipids, due to its low vapor pressure, its low acidity, and the formation of small crystals, although because of the strong background at low m/z, it precludes detection of species below approximately 500 Da. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 35 publications
(59 reference statements)
4
111
0
Order By: Relevance
“…The lipid images presented in Figure 1, from formalin fixed tissue, correspond well with previously published data [16,20,22,24,46,47,51,[54][55][56][71][72][73][74] and unpublished data obtained in this laboratory, for the analysis of lipid species directly from fresh rat brain sections. The three most commonly imaged lipid species within the rat brain to date, PC 34:1, PC 32:0, and PC 36:1, all display similar distributions to data published by Wang and co-workers shows an omnipresent distribution in the brain (data not shown), however, images of m/z 782 and 798, which represent the sodium and potassium adduct, respectively, show decreased ion counts within the corpus callosum and arbour vitae region of the cerebellum.…”
Section: Maldi-msi Of Formalin Fixed Rat Brain Sectionssupporting
confidence: 86%
See 2 more Smart Citations
“…The lipid images presented in Figure 1, from formalin fixed tissue, correspond well with previously published data [16,20,22,24,46,47,51,[54][55][56][71][72][73][74] and unpublished data obtained in this laboratory, for the analysis of lipid species directly from fresh rat brain sections. The three most commonly imaged lipid species within the rat brain to date, PC 34:1, PC 32:0, and PC 36:1, all display similar distributions to data published by Wang and co-workers shows an omnipresent distribution in the brain (data not shown), however, images of m/z 782 and 798, which represent the sodium and potassium adduct, respectively, show decreased ion counts within the corpus callosum and arbour vitae region of the cerebellum.…”
Section: Maldi-msi Of Formalin Fixed Rat Brain Sectionssupporting
confidence: 86%
“…There has been increasing interest in the field of lipidomics, which has led to significant research into the analysis and imaging of lipids in tissue sections by MALDI-MS [16,20,24,25,31,34,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. There is now considerable evidence that lipids are differentially expressed in normal and diseased tissue, and that they may play a central role in the pathologic processes associated with numerous disease states, including diabetes, Alzheimer's and dementia, cancer, heart disease, and numerous metabolic diseases [25,50,52,58,[60][61][62][63][64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). For endogenous substance detection, previous studies have demonstrated the efficiency of 2-MBT as a MALDI matrix for tissue analysis of lipids after application by spray deposition [40]. Its deposition by sublimation on fingermarks allows the detection of amino acids, sodiated wax esters, diglycerides (DAGs), triglycerides (TAGs), and some fatty acids, such as oleic and stearic acids (Supplementary Table 1).…”
Section: Evaluation Of Matrix Candidates For Sublimation and Imsmentioning
confidence: 99%
“…Despite the potential applicability of this method and the growing number of papers published recently in the field of lipid IMS [9][10][11], some questions remain unanswered and numerous concerns have been raised. Most importantly, it is not clear whether the different intensities of lipid signals in different tissues or areas of a tissue are indeed due to real differences in lipid concentrations, or rather to changes in the environment from which the lipids are extracted during the desorption process [12,13].…”
Section: Introductionmentioning
confidence: 99%